Systematic Literature Review of Sukuk Research in Esteemed Journals: Trends, Key Authors, and Institutional Affiliations - Alhamdania, Cintia Syafa; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to comprehensively examine the existing body of literature on Sukuk, focusing specifically on scholarly publications in esteemed international journals. Sukuk, an investment instrument compliant with Sharia principles, has been established by the government as a secure and accessible option that avoids engagement with prohibited components such as gambling and usury. The distinctiveness of this study resides in its novel methodology that integrates data analysis with content analysis, setting it apart from prior research endeavors. The employed study methodology entails a comprehensive literature evaluation, widely regarded as the optimal approach for synthesizing extant research findings. The primary objective of this study is to conduct a comprehensive thematic content analysis by employing the systematic literature review methodology and following the PRISMA approach. The analysis will be based on publications indexed in well-regarded worldwide databases, including Scopus. This study offers significant contributions to the advancement of knowledge in the field of Sukuk, hence facilitating future improvements in this area of research. This study aims to offer a comprehensive overview of Sukuk research conducted in several academic fields. According to the research findings, it is projected that the peak trend in Sukuk research will manifest in the year 2022. The preeminent author in this field is Hassan, M.K., while the primary institutional affiliation of most researchers is the International Islamic University Malaysia.